P-473 Low radiation affects follicle count in sheep ovaries. (30th June 2022) - Saueressig, R; Reiser, E; Frank, M; Tollinger, S; Haybäck, J; Ganswindt, U; Toth, B
Abstract: Study question: What is the effect of low dose radiation on follicle count in sheep ovaries? Summary answer: Even low dose radiation has a negative impact on the follicle count in sheep ovaries. What is known already: Radiotherapy is a corner stone of state-of-the-art cancer treatment, especially in young cancer patients. Survival rates are constantly rising, resulting in long-term survivors with potential child wish. High doses of radiation lead to a permanent damage to the ovaries. Little is known about the damage after low dose radiation to the ovaries including both follicles and stroma. Study design, size, duration: Prospective ongoing study, including n = 41 sheeps and 942 ovarian punches (Ø 3mm). So far, n = 12 sheep and n = 120 punches were analysed between April 2020 and January 2022. After finishing the experiments with sheep ovarian tissue, we will continue with a mouse model and human ovarian tissue. Participants/materials, setting, methods: 942 cortex punches out of a total of n = 41 sheep were obtained and cryopreserved. After thawing the punches were radiated with a dose of 0.0, 0.5, or 9.0 Gy using a cesium 137 radionuklide source (GSR C1, GammaService Medical GmbH). The punches were fixed in formalin, embedded in paraffin, cut into serial sections of 3-5 µm and stained with Hematoxylin and Eosin for follicle counting as well as Caspase 3 and Ki67. Main results and the role of chance: Follicle loss was already observed after low dose radiation (0.5 Gy). Mean follicle count after 0 Gy, 0.5 Gy, and 9 Gy were 7.5, 2.3 and 1.8, respectively. While after 0 Gy, no signs of degeneration were visible, after radiation with 9 Gy follicles showed strong signs of degeneration including disorganization of granulosa cells, pyknosis and stromal irregularities. Limitations, reasons for caution: Limitations of our study include the pilot character and therefore small sample size. The presented data only display part of the overall project including also an in-vivo mouse model. Wider implications of the findings: As even low dose radiation seems to damage ovarian follicles, further in-vivo studies are needed to confirm these results. Moreover, fertility preservation methods need to be offered consequently to young cancer patients receiving radiotherapy. Trial registration number: 25